Toward Islamic English by Ismā‘īl Rājī al Fārūqī - ZEESHAN AHMED SHEIKH (Hamdard Islamicus, 2023)
Dr. Ismā‘īl Rājī al Fārūqī (1339-1406 A.H/1921-1986 A.C) is widely recognized as an authority on Islam and comparative religion. Dr. al Fārūqī was a dedicated and active academician. His educational training in Philosophy took place at Indiana and Harvard University. He also engaged in the post-graduate study of Islam at al-Azhar University and Christianity and Judaism at McGill University. He co-founded the International Institute of Islamic Thought (IIIT) and the Association of Muslim Social Scientists (AMSS). Among his significant intellectual and academic contributions is his consistent emphasis on the Islamization of knowledge and result-oriented inter-faith dialogues. The present book, Toward Islamic English, extends the same discourse on the Islamization of knowledge. However, the paradigm in which the book’s theme is described is more academic and relates to the methodological dimensions of studying Islamic Studies as an academic discipline.